TRANSGREDINDO A NORMA PARA SE COMUNICAR:O CASO DOS RADICAIS GRECO-LATINOS NA FORMAÇÃO DOS NEOLOGISMOS DO PORTUGUÊS CONTEMPORÂNEO - Pilla, Éda Heloisa (Organon, 2012)
The article deals with the coinage of new words in contemporary Portuguese using the secondarymeaning of Greek and Latin afixes such as “tele-”, “audio-” , “foto-” and “radio-”. The new semic combination ofthose radicals, formed through the sociolinguistic dimension of language, proves, once more, that creation ofneologisms belongs to the syncrony of language.